Peptide Transporters in the Primary Gastrointestinal Tract of Pre-Feeding Mozambique Tilapia Larva - Con, Pazit; Nitzan, Tali; Slosman, Tatiana; Harpaz, Sheenan; Cnaani, Avner (Frontiers in Physiology, 2019)
Fish larvae differ greatly from the adult form in their morphology and organ functionality. The functionality of the gastrointestinal tract depends on the expression of various pumps, transporters and channels responsible for feed digestion and nutrients absorption. During the larval period, the gastrointestinal tract develops from a simple closed tube, into its complex form with differentiated segments, crypts and villi, as found in the adult. In this study, we characterized the expression of three peptide transporters (PepT1a, PepT1b, PepT2) in the gastrointestinal tract of Mozambique tilapia (Oreochromis mossambicus) larvae along 12 days of development, from pre-hatching to the completion of yolk sac absorption. Gene expression analysis revealed differential and complimentary time-dependent expression of the PepT1 variants and PepT2 along the larval development period. Immunofluorescence analysis showed differential protein localization of the three PepTs along the gastrointestinal tract, in a similar pattern to the adult. In addition, PepT1a was localized in mucosal cells in the larvae esophagus, in much higher abundance than in the adults. The results of this study demonstrate specialization of intestinal sections and absorbance potential of the enterocytes prior to the onset of active exogenous feeding, thus pointing to an uncharacterized function and role of the gastrointestinal tract and its transporters during the larval period.